OPPORTUNITIES FOR IMPROVING THE PAYMENT SYSTEM IN TAX ADMINISTRATION (American Journal of Business Management, Economics and Banking, 2026)
This article examines the current state and future opportunities for improving the tax payment system through digital transformation and technological integration. The research analyzes the transition from traditional, manual-based tax administration to modern "Tax Administration 3.0" frameworks, emphasizing the role of real-time data processing, API-based banking integrations, and artificial intelligence in reducing the tax gap. By utilizing comparative analysis and longitudinal data, the study identifies that the digitalization of tax services significantly lowers compliance costs for businesses while enhancing state revenue stability. The findings suggest that "invisible taxation"—where fiscal obligations are seamlessly embedded into commercial software—represents the most effective pathway for fostering voluntary compliance and ensuring long-term fiscal sustainability in the digital economy.